Knowledge and practices of dairy farmers about environmental health: Need for eco-health approach in Punjab - Singh, Harmandeep; Singh, Jaswinder; Kansal, SK; Verma, HK (Indian Journal of Dairy Science, 2021)
The dairy industry impacts environmental health in various ways and the extent of the impact depends upon the knowledge and practices of dairy farmers. This research surveyed the knowledge and practices of the dairy farmers (n-300) towards environmental safety from five different agro-climatic zones of Punjab (India). Data were analyzed using SPSS software through descriptive statistics, Chi-square test of independence with Cramerâ€™s V value as measures of effect size. Analysis of variances, followed by Games Howell post hoc test was performed to analyze subgroup differences amongst explanatory variables. The majority of farmers (57.66%) had a low knowledge score on environmental safety. Majority of farmers did not know greenhouse gasesÂ emission (81%) from dairy animals/their excreta, the impact of dairy farming on climate change (86.67%), and were not treating farm effluents before discharging them into the environment (92.67%). Climate change (I) followed by air pollution (II), human-animal-environment interaction (III), water pollution (IV), and soil pollution(V) were the rank-wise factors reported to affect dairy farming. Further, socio-demographic and farm characteristics have a positive influence on the farmerâ€™s knowledge. The study warrants an extensive awareness campaign on scientific cum eco-friendly dairy farming with an emphasis on measures to reduce environmental pollution and an eco-health approach to bridge the knowledge hiatus.